2020
DOI: 10.1371/journal.pone.0231505
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney disease stage predicts outcome of patients on extracorporeal membrane oxygenation support

Abstract: Background The mortality rate of patients on extracorporeal membrane oxygenation (ECMO), especially those patients that develop acute kidney injury (AKI) is high. Acute kidney disease (AKD) is a term used to describe the continuum from AKI to chronic kidney disease. However, the role of AKD in predicting the prognosis of patients on ECMO support is unclear. Methods A total of 168 patients who received ECMO support and survived for more than 7 days at a single hospital from 2003 to 2008 were enrolled for this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…This new definition separates AKI and AKD as they reflect the severity of patient’ renal function injury within the first 6 days and 7-90 days after an AKI initiating event respectively, which is able to show the dynamic nature of renal function and natural course of the disease. Most studies on AKD so far took the definition by 2012 KDIGO AKI workgroup and targeted on AKD patients with or without AKI ( Fujii et al, 2014 ; Hsu et al, 2020 ; James et al, 2019 ; Mima et al, 2019 ; Patimarattananan et al, 2020 ). The studies found that AKD patients not meeting the AKI criteria were associated with higher risks of developing new CKD, end stage kidney disease and death compared with patients without kidney injury ( Fujii et al, 2014 ; Hsu et al, 2020 ; James et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This new definition separates AKI and AKD as they reflect the severity of patient’ renal function injury within the first 6 days and 7-90 days after an AKI initiating event respectively, which is able to show the dynamic nature of renal function and natural course of the disease. Most studies on AKD so far took the definition by 2012 KDIGO AKI workgroup and targeted on AKD patients with or without AKI ( Fujii et al, 2014 ; Hsu et al, 2020 ; James et al, 2019 ; Mima et al, 2019 ; Patimarattananan et al, 2020 ). The studies found that AKD patients not meeting the AKI criteria were associated with higher risks of developing new CKD, end stage kidney disease and death compared with patients without kidney injury ( Fujii et al, 2014 ; Hsu et al, 2020 ; James et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…AKI and AKD reflect renal function status in different time periods during the disease process. Although studies have shown that AKD is associated with increased risks of mortality and renal function decline after hospital discharge ( Hsu et al, 2020 ; James et al, 2019 ; Kofman et al, 2019 ; Matsuura et al, 2020 ; Mizuguchi et al, 2018 ), few targeted on patients with AKD after AKI, and the epidemiology of hospitalized patients with AKD after AKI is largely unknown. Whether AKD acts as an important intermediate stage for progression to renal dysfunction, chronic dialysis and mortality after AKI remains to be found.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in critically ill patients with septic AKI estimated that AKD occurred in between 27 and 32% of patients, but was not associated with an increased risk of death at up to 1 year compared to patients with AKI alone [7, 13]. In cardiac populations, it has been reported that as many as 48% of patients admitted to coronary care, 47% of patients on extracorporeal membrane oxygenation, and 11% of patients undergoing cardiac surgery developed AKD [10, 12, 15]. Similar to our results, these studies found that survival between 90 days and 5 years in patients with AKD was significantly worse compared to those with NKD, as was eGFR at 2 years.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Despite this, AKD has not been systematically studied, and its relationship with long-term clinical outcomes is poorly understood. Data from previous studies have been variably limited by short follow-up time [7, 8], non-consensus definitions of exposure [7-11], clinically enriched populations [10, 12-16], lack of adjustment for confounders [7, 9, 12, 14-16], and pooling of heterogeneous data from community and hospital settings [17]. The only published study to examine AKD without AKI included patients with unknown baseline kidney function [17].…”
Section: Introductionmentioning
confidence: 99%
“…All three patients with AKI underwent mechanical ventilation and ECMO, and it was difficult to distinguish whether AKI was caused by SARS-CoV-2 infection or was associated with treatments, such as ECMO and vancomycin. 24 25 Therefore, it is possible that the incidence of AKI related to COVID-19 was overestimated. In fact, all three patients used both ECMO and vancomycin, and AKI developed after vancomycin use.…”
Section: Discussionmentioning
confidence: 99%